Complexity, knowledge and education: the emergence of a new epistemological paradigm in contemporary context - Sidinei Pithan da Silva (Universidade Federal de Santa Maria, 2015)
This study addresses the emergence of a new epistemological paradigm in the contemporary scenery, which points to the problem of complexity involved in the whole human knowledge dynamic. The methodological approach is guided by a hermeneutic and dialectical perspective, which intends to privilege the critical reading from Edgar Morin books, placing them in a set of reading and trying to extract the relation between epistemological, ethical and political concepts. The result of this reading, when thematized in the school place, is to understand the school's new challenge in dealing with knowledge. Besides teaching knowledge, the school needs to teach a new relation with knowledge. This presupposes a mediate and complex understanding of reality, reworking the science and knowledge meaning in the corporate context.